SARS-CoV-2 spike protein mutation variants: Recent advances in theragnostic and vaccines development - Jutishna Bora; Akash Deep; Archana Dashmana; Smita Lata; Shailendra Thapliyal; Nayan Talukdar; Ravi K. Deshwal; Sarvesh Rustagi; Sumira Malik (Microbes and Infectious Diseases, 2025)
Background: COVID-19, caused by SARS-CoV-2 and linked to over 6.5 million deaths, has severely disrupted global healthcare systems with long-lasting impacts. Developing effective vaccines and treatments requires a deep understanding of host-virus interactions. Designing new tactics to reduce the consequences of the developing variations of concern (VOC) requires an understanding of the evolution of the virus and the effects of genetic variation on host immune evasion and vaccination efficacy. New SARS-CoV-2 variants, commonly classified as variants of interest (VOI), have been identified based on factors such as their ability to spread, the severity of illness they cause, and their potential to evade detection and immune responses. Due to its special ability to attach to host receptors, generally preserved nature, high immunogenicity in inducing neutralizing antibodies, and suitability as a target of T-cell responses, the spike protein is the focus of most vaccines currently being developed and/or used. Emerging SARS-CoV-2 strains, however, are showing variations in the spike protein, which may influence the effectiveness of vaccines and antibody-based treatments. In addition to strengthening viral immune evasion mechanisms. Currently, there is a lot of interest in how mutations in the spike protein affect immunity and vaccination, and how well the available vaccines protect against newly emerging variants. This review covers the effects of SARS-CoV-2 spike protein mutations on immune evasion and vaccine-induced immunity as well as future directions that may help with studies concentrating on developing efficient and novel vaccines and/or immunotherapy strategies that take viral evolution into account